Goniometric Evaluation and Passive Range of Joint Motion in Chondrodystrophic and Non-Chondrodystrophic Dogs of Different Sizes - Reusing, Mhayara; Brocardo, Mayara; Weber, Saulo; Villanova, José, Jr. (VCOT Open, 2020)
Objective This study aimed to evaluate angle values in maximal flexion and extension; the passive range of motion (PROM) of the shoulder, elbow, carpal, hip, stifle and tarsus; and the carpal abduction and adduction of chondrodystrophic (CD) and non-chondrodystrophic (NCD) dogs of different sizes.Study Design Goniometric evaluation was performed in triplicate using a universal goniometer. CD dogs were categorized into miniature, small, medium, large and giant sizes, whereas NCD dogs were allocated to small- and medium-size groups. Hence, each of the seven subgroups comprised 11 clinically healthy dogs. For data analysis, the Levene test was used to evaluate homoscedasticity. The means of each joint angle with the means in each group as well as the PROM between the CD and NCD groups was compared by the Student's t-test; meanwhile, the means of the joint angles and ROM among the sizes were compared by analysis of variance, followed by the Tukey test. In those cases, when no homogeneity variance was observed, the Bonferroni test was used. In every case, p ≤ 0.05 was considered significant.Results The articular angles and PROM differed according to the dog size and type, that is, CD or NCD.Conclusion The goniometric values and PROM of dogs depend on the joint type, dog size and chondrodystrophy status. Further studies are necessary to increase the accuracy of the results and to establish the predominant factors governing the differences discovered.
Keywords: dog; goniometry; chondrodystrophy; passive range of motion